Enhancing Quality of Management Education in the Average Indian Business School Through Shared Responsibility - Bohra, Narendra Singh (Prabandhan: Indian Journal of Management, 2013)
The Management education market in India has taken rapid strides during the last two decades, a post graduate qualification in management has been perceived as the passport to a fruitful and financially beneficial corporate career. This resulted in massive demand for higher education in management and true to orthodox economic theory; there has also been a corresponding supply response. However MBA/PGDM education now appears to be a victim of its own success. Deterioration in the quality of management graduates has contributed to a corresponding lowering of the job profile, a gradually emerging job market which considers MBA/PGDM degree merely as an entry level graduate qualification. Unsurprisingly, the compensation package has also reflected the changed job profile. This research paper is an attempt to focus on the root causes of low grade management education in average business schools in India, and also aimed to explore the responsibilities of average B-Students and B-Schools to overcome with this unwanted situation.